Respostas
respondido por:
2
3x² + 4x + 1 = 0
Δ: b² - 4.a.c
Δ: 4² - 4 . 3 . 1
Δ: 16 - 12
Δ: 4
![x' = \frac{- 4 + \sqrt{4} }{2.3} = \frac{-2}{6} \\\\ x'' = \frac{ - 4- \sqrt{4} }{2.3} = \frac{-6}{6} = -1 x' = \frac{- 4 + \sqrt{4} }{2.3} = \frac{-2}{6} \\\\ x'' = \frac{ - 4- \sqrt{4} }{2.3} = \frac{-6}{6} = -1](https://tex.z-dn.net/?f=x%27+%3D+%5Cfrac%7B-+4+%2B+%5Csqrt%7B4%7D+%7D%7B2.3%7D+%3D+%5Cfrac%7B-2%7D%7B6%7D+%5C%5C%5C%5C+x%27%27+%3D+%5Cfrac%7B+-+4-+%5Csqrt%7B4%7D+%7D%7B2.3%7D+%3D+%5Cfrac%7B-6%7D%7B6%7D+%3D+-1+)
Δ: b² - 4.a.c
Δ: 4² - 4 . 3 . 1
Δ: 16 - 12
Δ: 4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás